Serum Asymmetric Dimethylarginine, Nitrate, Vitamin B12, and Homocysteine Levels in Individuals with Pulmonary Embolism - Murat Altuntaş; Figen Atalay; Murat Can; Remzi Altın; Meltem Tor (Mediators of Inflammation)
We aimed to analyze the pre- and posttreatment serum asymmetric dimethylarginine (ADMA), nitrate (NO3), vitamin B12 and homocysteine levels in pulmonary embolism (PTE) patients and to determine the prognostic value of these variables in predicting chronic thromboembolic pulmonary hypertension (CTEPH). This study was conducted in 64 patients. The patients were classified into the two groups: patients with normal pulmonary artery pressure (PAP) (group I) and patients with high PAP with persistent lung perfusion defects or who died at the end of 3 months of therapy (group II). We found statistically significant differences between two groups with respect to the partial oxygen pressure, the oxygen saturation, and the PAP, but there was no difference between the two groups with respect to the pretreatment ADMA, NO3, or homocysteine levels. The vitamin B12 levels were higher in group II. The NO3 levels increased and the ADMA and vitamin B12 levels decreased with treatment in both groups. These results suggest that these parameters are not predictive of the development of CTEPH.